Application of Goal Programming Method in Production Optimization of Crude Palm Oil and Crude Palm Karnel Oil (Case Study: Pt. Barumunagro Sentosa) - Rizwana, Annisa; Nasution, Putri Khairiah (JMEA : Journal of Mathematics Education and Application, 2023)
Planning in production is an action from a company that can determine the success of a company. PT. BarumunAgro Sentosa is a company that owns palm oil plantations and mills. This study aims to analyze the methodGoal Programming and its completion in production planningCrude Palm OilandCrude Palm Kernel Oil in the period January – December 2022 Completion of the methodGoal Programming in optimizing the production of CPO and CPKO in this study using the help of LINDO software (Linear Interactive Discrete Optimizer). Completion of this method first performs a projection or forecast of the number of requests obtained from the previous period's demand data with Minitab software. The results obtained from this study are that the optimal amount of CPO production for the period January - December 2022 is 74,803,459 kg from the initial target of 73,420,955 kg and for the optimal amount of CPKO production for the period January - December 2022 is 7,058,777 kg from the initial target of 5,937. 531 kg.. The total production of CPO and CPKO has no deviation so that the production of CPO and CPKO can be said to be optimal.